Chronic hip pain in adults: Current knowledge and future prospective - Vanita Ahuja; Deepak Thapa; Sofia Patial; Anjuman Chander; Anupam Ahuja (Wolters Kluwer Medknow Publications, 2020)
Chronic hip pain is distressing to the patient as it not only impairs the daily activities of life but also affects the quality of life. Chronic hip pain is difficult to diagnose as patients often present with associated chronic lumbar spine and/or knee joint pain. Moreover, nonorthopaedic causes may also present as chronic hip pain. The accurate diagnosis of chronic hip pain starts with a detailed history of the patient and thorough knowledge of anatomy of the hip joint. Various physical tests are performed to look for the causes of hip pain and investigations to confirm the diagnosis. Management of chronic hip pain should be mechanistic-based multimodal therapy targeting the pain pathway. This narrative review will describe relevant anatomy, causes, assessment, investigation, and management of chronic hip pain. The focus will be on current evidence-based management of hip osteoarthritis, greater trochanteric pain syndrome, meralgia paresthetica, and piriformis syndrome. Recently, there is emphasis on the role of ultrasound in interventional pain procedures. The use of fluoroscopic-guided radiofrequency in periarticular branches of hip joint has reported to provide pain relief of up to 36 months. However, the current evidence for use of platelet-rich plasma in chronic hip osteoarthritis pain is inconclusive. Further research is required in the management of chronic hip pain regarding comparison of fluoroscopic- and ultrasound-guided procedures, role of platelet-rich plasma, and radiofrequency procedures with long-term follow-up of patients.